Performance study of the coexistence of wireless sensor networks (WSN) and wireless local area networks (WLAN) - Haron, Muhammad Adib (Institute of Electrical and Electronics Engineers, 2008)
This paper presents a special state machine of interference temperature multiple access (ITMA) that characterizes both interference and noise with single parameter in wireless sensor networks (WSN) application. By measuring current interference temperature before data transmission, cognitive node is able to determine transmit power and data rate that should be used to achieve desired capacity without violating interference temperature limit at other co-channel transceiver. Simulations of NS-2 are shown to simultaneously satisfy the three main objectives of extending battery life of cognitive node through optimum transmit power provision, maximizing the traffic carrying of networks capacity and limit interference to other coexist node. Hence, cognitive node is feasible to support QoS provisioning, and fairness among WSN and WLAN users.